Governance decisions and tourism resource conservation in Tanzania: A political economy perspective - Ladislaus Batinoluho (School of Tourism, Universitas Ciputra Surabaya, 2026)
Despite Tanzania’s strong policy and legal frameworks for sustainable tourism and community-based conservation, little is known about how governance decisions affect tourism resource conservation. This study examines how political economy dynamics shape these decisions using qualitative methods, including interviews, focus groups, and document review across Tanzania’s four tourism circuits. Findings reveal highly centralized governance with limited local fiscal and decision-making autonomy, constraining community participation and adaptive management. Political incentives and revenue-driven performance targets prioritize short-term economic gains over long-term ecological sustainability. Power asymmetries favor investors and central authorities, resulting in inequitable benefit-sharing and reduced local support, while weak transparency and limited institutional capacity undermine trust in governance mechanisms such as Wildlife Management Areas. Effective conservation requires aligning political incentives with ecological goals, strengthening local capacity, and fostering meaningful community participation. Limitations include qualitative focus and partial coverage. Future research should examine long-term governance impacts, tourism taxation, and regional comparative analyses to identify best practices in sustainable tourism governance.